2021
DOI: 10.3390/cells10113238
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiles of Cell Fate Transitions Reveal Early Drivers of Neuronal Apoptosis and Survival

Abstract: Neuronal apoptosis and survival are regulated at the transcriptional level. To identify key genes and upstream regulators primarily responsible for these processes, we overlayed the temporal transcriptome of cerebellar granule neurons following induction of apoptosis and their rescue by three different neurotrophic factors. We identified a core set of 175 genes showing opposite expression trends at the intersection of apoptosis and survival. Their functional annotations and expression signatures significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(31 citation statements)
references
References 105 publications
(114 reference statements)
4
27
0
Order By: Relevance
“…Despite little is known about the specific role of Maf in neuronal apoptosis and degeneration, recent reports suggest that over-expression of this gene can cause cell death probably through a p53-mediated signaling [122,137]. In agreement with these results, we found an early and transient peak of transcription for Maf following induction of CGNs apoptosis, while its expression decreased following treatment with NFs (Figures 1 and 3) [43]. As other oxidative stress reactive proteins, Maf has been implicated in various neurological disorders, including Alzheimer's and Parkinson's diseases, and its role is emerging as a novel target in the treatment of these disorders [138][139][140].…”
Section: Musculoaponeurotic Fibrosarcoma (Maf)supporting
confidence: 90%
See 4 more Smart Citations
“…Despite little is known about the specific role of Maf in neuronal apoptosis and degeneration, recent reports suggest that over-expression of this gene can cause cell death probably through a p53-mediated signaling [122,137]. In agreement with these results, we found an early and transient peak of transcription for Maf following induction of CGNs apoptosis, while its expression decreased following treatment with NFs (Figures 1 and 3) [43]. As other oxidative stress reactive proteins, Maf has been implicated in various neurological disorders, including Alzheimer's and Parkinson's diseases, and its role is emerging as a novel target in the treatment of these disorders [138][139][140].…”
Section: Musculoaponeurotic Fibrosarcoma (Maf)supporting
confidence: 90%
“…Several studies, in fact, have demonstrated that activation of Olig2 in response to different NFs (e.g., FGF, GDNF and PDGF) exerts protective and pro-survival effects in multiple neuronal types [155][156][157][158]. According with these findings, we observed an increased expression of Olig2 during CGNs rescue by Pacap, Igf1 and SP (Figures 1 and 3) [43]. Despite the role elicited by Olig2 in the adult cerebral cortex under pathological conditions is not yet known, its reduced expression seems to switch cell fate from differentiation to death, contributing to the development of psychiatric disorders and acute/chronic neurodegenerative diseases, including Alzheimer's disease and Amyotrophic Lateral Sclerosis, while its increased expression has been associated with different brain tumors, supporting its potential utility as therapeutic target for the treatment of both cancer and neurodegeneration [159][160][161][162][163][164][165][166][167][168][169][170][171].…”
Section: Oligodendrocyte Transcription Factor2 (Olig2)supporting
confidence: 79%
See 3 more Smart Citations